2011
DOI: 10.1016/j.econedurev.2010.12.003
|View full text |Cite
|
Sign up to set email alerts
|

What will I be when I grow up? An analysis of childhood expectations and career outcomes

Abstract: Abstract:In this paper we utilise the British National Child Development Study to explore the determinants of children's career expectations formed at the age of sixteen. We analyse how such career expectations impact upon human capital accumulation at the same age. We also analyse the extent of any divergence between childhood career expectations and the actual career outcomes experienced by the individuals at three distinct ages in adulthood (23, 33 and 42) as well as the impact of any such divergence on ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…It is apparent that gender has a very large effect upon occupational expectations. There are also distinct differences in terms of the magnitude of the association between education and career expectations across genders [26].…”
Section: Career Expectation Influences Career Developmentmentioning
confidence: 99%
“…It is apparent that gender has a very large effect upon occupational expectations. There are also distinct differences in terms of the magnitude of the association between education and career expectations across genders [26].…”
Section: Career Expectation Influences Career Developmentmentioning
confidence: 99%
“…Family, media and "people who are already doing the job" seem to have most impact on students' career decisions. This contrad icts a study [21] of past cohort data which suggested the teacher was the greatest influence on their students' career decisions. This could indicate that any intervention programme to reverse the current trends in computing should involve families and media, while any product to challenge misperceptions should present people from the computing industry as role-models.…”
Section: E Awareness Oftypical Rolesmentioning
confidence: 68%
“…Another study [20] summ arises the findings of Eccles et al (1999): "values attached to relevant job characteristics were significant predictors of teenage career aspirations". An analysis [21] of career expectations formed at age 16, concludes that, while a teacher's description of an occupation is influential, school resources devoted to careers advice "have limited influence on children's career expectations". That some of this data comes from the 1970s suggests a longstanding tradition of teachers being influential in their students' career choices.…”
Section: A Comparisons With Other Countriesmentioning
confidence: 98%
“…First, having labor market-related experiences (or the perception of experiences) related to labor market participation increases the likelihood of youth becoming employed upon graduation (Doiron & Gørgens, 2008). Also, teachers' expectations and relationships strongly influence youths' expectations about and probability of pursing specific careers after graduation (Brown, Ortiz-Nun˜ez, & Taylor, 2011). Thus, ICT-based instruction and STEM-related experiences potentially contribute to labor market participation and productivity.…”
Section: The (Non-)national Contextmentioning
confidence: 97%